Pembrolizumab for Patients with Relapsed or Refractory Extranodal NK/T-Cell Lymphoma in Korea - Lee, Ji Yun; Kwon, Ji Hyun; Hur, Joon Young; Yi, Jun Ho; Lee, Ji Hyun; Cho, Hyungwoo; Do, Young Rok; Jo, Jae-Cheol; Kang, Hye Jin; Koh, Yougil; Lee, Won Sik; Lim, Sung Nam; et al. (Cancer research and treatment, 2024)
Purpose Programmed death-1 blockade with pembrolizumab has shown promising activity in relapsed/refractory (R/R) extranodal natural killer/T-cell lymphoma (NKTCL), but studies are limited, with small patient numbers.Materials and Methods Thirteen institutes involved with the Consortium for Improving Survival of Lymphoma, a Korean lymphoma study group, collected the clinical data of 59 patients treated with pembrolizumab as salvage therapy between 2016 and 2022.Results The median age of the patients was 60 years (range, 22 to 87 years), and 76.3% had advanced Ann Abor stage disease. Pembrolizumab was given to 35.6%, 40.7%, and 23.7% of the patients as second-, third-, and fourth- or higher-line chemotherapy, respectively. The overall response rate was 40.7%, with 28.8% having complete response. The estimated 2-year progression-free survival (PFS) and overall survival rates for all patients were 21.5% and 28.7%, respectively; for responders, the rates were 53.0% and 60.7%, respectively. Although not statistically significant, Eastern Cooperative Oncology Group performance status ≥ 2 (hazard ratio [HR], 1.91; 95% confidence interval [95% CI], 0.93 to 3.94; p=0.078) and stage III or IV disease (HR, 2.59; 95% CI, 0.96 to 6.96; p=0.060) were associated with a trend toward shorter PFS in multivariate analysis. Grade 3 or 4 adverse events (AEs) were noted in 12 patients (20.3%); neutropenia (10.2%), fatigue (6.8%), and pneumonitis (5.1%) were most common AEs.Conclusion In conclusion, while pembrolizumab had a modest effect on patients with R/R NKTCL, it may be a useful salvage therapy for patients with localized disease and good performance status.